Soil Permeability in Different Types of Traditional Land use in Niukbaun Village, West Amarasi, NTT - Ndun, Astrid Aryani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Traditional land use is a method of land use that has been carried out for generations by the community. Land management activities carried out from generation to generation, with the same pattern from year to year, such as land use which is often called Tebas Bakar and Mamar. Both land uses with different management methods can indicate changes in soil conditions as a medium for plant growth in their physical properties. The purpose of this study was to determine soil permeability in traditional land cultivation activities in Niukbaun Village, West Amarasi, NTT. Field and laboratory research was carried out in August-October 2024. The research location was in Niukbaun Village, West Amarasi District, with the traditional Tebas Bakar and Mamar management systems. Research Methods Data collection includes primary data, secondary data, Permeability observations were carried out in the field using a permeameter. The results obtained: Soil permeability on mamar land is better than slash and burn land. Each type of traditional land use differs according to its management method. So that texture, organic material and land use processing have an influence on the size of the soil permeability.